Variation within and across Romance languages : selected papers from the 41st Linguistic Symposium on Romance languages (LSRL), Ottawa, 5-7 May 2011 - Côté, Marie-Hélène; Mathieu, Eric, 1967- (Amsterdam studies in the theory and history of linguistic science. Series IV. Current issues in linguistic theory, 2014)
Testing oral proficiency is an important but challenging part of foreign language assessment: currently accepted methods are time-consuming and expensive. Our recent efforts have led to the implementation of new assessment methods for English (Graham et al. 2008), Japanese, and Spanish. We demonstrate that this work is also relevant for French oral proficiency testing. We begin by describing and historically situating an oral proficiency testing methodology called elicited imitation (EI). Then, we document the development, implementation and evaluation of a French EI test. We also detail the i.